APLIKASI PENGENALAN OBJEK WISATA SEJARAH KOTA TUA JAKARTA BERBASIS AUGMENTED REALITY - Agung Selamet Riadi; anton anton; Ummu Radiyah (Universitas Islam Lamongan, 2018)
The world of tourism in Indonesia, especially DKI Jakarta, has developed rapidly. One of the tourism object in Jakarta is Old Town tour (Kota Tua). About thirty percent of visitors who came to the Kota Tua area, generally come only to take pictures, bike or just gather. To provide a unique experience and historical knowledge to tourists, an application of augmented reality is made that can be used by tourists when visiting Jakarta's Kota Tua area. In the application created there are three-dimensional objects, photos, as well as general informationsand historical informations of attractions in the Kota Tua Jakarta. The method of this research using waterfall model as a system development model with five stages namely Requirement Analysis, System Design, Implementation, Integration and Testing, Operation and Maintenance.